To Study the Maternal and Neonatal Outcome in Postdated Women Undergoing Induction of Labour Versus Spontaneous Labour - Dagli, Setu (J Obstet Gynaecol India, 2021)
INTRODUCTION: Ensuring safety of the mother along with the delivery of a healthy baby is the ultimate objective of all obstetricians. Labour induction is increasingly becoming one of the most common obstetric interventions in India. The aim of the study is to compare the feto-maternal outcome of induction of labour versus spontaneous labour in postdated women. METHOD: This was a prospective observational comparative study. A total of 100 patients were selected, 50 who had induction of labour (study group) and 50 who had spontaneous labour (control). A structured proforma and partographs were used to obtain data. RESULT: 42% nulliparous women had induction of labour as compared to 29% multiparous women. The rate of cesarean section (58%) was substantially higher in those who had been induced. Non-progression of labour or failure of induction was the commonest indication for cesarean section. Post-partum haemorrhage was a complication found more commonly in the study group. Perineal tears were found more commonly in the control group. The mean birth weight of babies born to mothers who had been induced was significantly higher than that of those born to women who went into spontaneous labour. The APGAR scores were comparable in both groups. There was a higher incidence of hyperbilirubinemia in the study group. CONCLUSION: Although induction of labour is a relatively safe procedure, some foetal and maternal risks were found to be higher in induced group than in those with spontaneous labour. Induction must be carried out only when necessary and not as a routine elective procedure.